DAMPAK PEMBELAJARAN BAHASA INGGRIS TERHADAP PEMAHAMAN DAN PENGAMALAN NILAI-NILAI PENDIDIKAN AGAMA ISLAM PADA MAHASISWA - Heriady Heriady (Jurnal Risalah Addariyah: Studi Ilmu-Ilmu Keislaman, Pendidikan dan Sosial Kemasyarakatan, 2024)
In this globalization era, English skills are becoming increasingly important, including in Islamic colleges. Material related to Islamic Education (PAI) taught in college also has literature written in English. Therefore, it is important to know whether learning English can influence students' ability to access literature on English PAI. This research aims to analyze the impact of learning English on the ability of STAI DDI Mangkoso students to access Islamic Religious Education material in English. This research uses a qualitative approach with descriptive-analytical methods. The research informants consisted of students from the PAI program of STAI DDI Mangkoso who had participated in the English learning program for two semesters. Data was collected through in-depth interviews, participant observation, and document study. The data analysis technique is carried out through three stages, namely: data reduction, data presentation, and verification or conclusion. The results showed that learning English at STAI DDI Mangkoso had a positive impact on students' ability to access literature of English PAI material. However, some students feel that learning English does not have a significant impact on students' ability to access the literature of PAI in English. It is hoped that the results of this research will provide a better understanding of the impact of English language learning on students' ability to access literature of English PAI material